Preparation and Characterization of Hydroxyapatite by the precipitation method and heat treatment (Research, Society and Development, 2020)
Hydroxyapatite is a synthetic substance in the form of microspheres composed of calcium and phosphate, present in human bones and tooth enamel. The objective of the work was to synthesize hydroxyapatite, from the solution of calcium nitrate and diamonic phosphate by the method of precipitation and heat treatment, obtaining the hydroxyapatite in powder form. To study its structural evolution, Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) and Raman spectroscopy were used. The results show that the hydroxyapatite nanocrystalline can be successfully produced by the precipitation technique from raw materials.